Design and analysis of an 8-bit SAR analog-digital converter - Wang, Ting. (2009)
This report describes the author‘s final year project in the Circuits and Systems of Electrical and Electronic Engineering School in Nanyang Technological University. The main objective of this project is to analyze and develop the circuit design of an 8-bit Successive Approximation Register (SAR) Analog-to-digital Converter (ADC) using the Charter 0.18um processing technique. The design tool used is the Cadence Virtuoso schematic editor and Virtuoso Spectre simulator.